Pharmacokinetic study of single and multiple oral administration of glutamine in healthy Beagles - Guo, Fanxi; Liu, Dongying; Zhou, Yuqing; Yu, Yuanqian; Xu, Yidan; Zou, Yuanpeng; Li, Chongyang; Zhang, Fengyichi; Yu, Zugong (Frontiers in Pharmacology, 2022)
Glutamine is an amino acid that is mainly used for the treatment of gastrointestinal diseases in clinic, but there is a lack of such medicine in veterinary clinic, and its research in dogs has never been seen. This study aimed to investigate the pharmacokinetics of single and multiple administration of glutamine (Gln) tablets in Beagles. Twenty-four healthy Beagles were randomly selected for the pharmacokinetic study of a single dose of low (120 mg/kg), medium (240 mg/kg), and high (360 mg/kg) Gln tablets. After 7 days of washout period, six Beagles in the medium group were selected for a multiple-dose pharmacokinetic study, 240 mg/kg twice a day for 7 days. The Gln concentration in plasma was determined by a validated UPLC-MS/MS method. The results of single oral administration of different doses of Gln tablets showed that Cmax, AUC0→t, AUC0→µ had a certain linear relationship with the dosage. T-tests were performed for single and multiple administration of Tmax, Cmax, t1/2λz, AUC0→t, and AUC0→µ, and the results showed no significant differences (P>0.05). Therefore, Gln tablets were absorbed quickly by oral administration, and there was no accumulation in Beagles after 7 days of administration.